"Liver as excretory organ": Developing Android-based flash learning media for middle school students - Yasmine Salsabila Muninda; Yuni Pantiwati; Elly Purwanti; Tutut Indria Permana (Research and Development in Education (RaDEn), 2021)
Studying the liver as an excretory organ is still a problem for students. The availability of learning media that can represent learning is urgently required. This study aims to develop and analyze the feasibility and practicality of Android-based flash learning media on the liver as an excretory organ for eighth-grade students. This Research and Development (R&D) uses the Borg and Gall model with a limit of up to stage seven. The results of expert validation show that learning media is included in the "very feasible" category according to media experts and material experts, with the percentage order of 86% and 95%. The media practicality by the teacher's response showed that media was categorized as very practical (94%). Then, student response toward the media was reached 85% and categorized as practical. The test of the effectiveness of learning media on critical thinking skills showed that there was a significant difference between the pretest and posttest scores. The results of this study need to be continued at the next R&D stage to get the feasible product.